Methodology of identifying critical objects of infrastructure; Методология проектирования молодежного научно-инновационного пространства как основа подготовки современного инженера - Babkin S. D. (Integrity of traditions and innovations as the basis for the development of modern engineering science, 2014)
Заглавие с экрана